2021
DOI: 10.3390/s21124062
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Indoor People Presence in Buildings Using Low-Cost Infrared Sensor Array in Doorways

Abstract: We propose a device for monitoring the number of people who are physically present inside indoor environments. The device performs local processing of infrared array sensor data detecting people’s direction, which allows monitoring users’ occupancy in any space of the building and also respects people privacy. The device implements a novel real-time pattern recognition algorithm for processing data sensed by a low-cost infrared (IR) array sensor. The computed information is transferred through a Z-Wave network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In ref. [30], the authors used infrared (IR) sensors to calculate the number of people inside a building, installing sensors on the doors' tops to detect transit movement between rooms, so they could calculate how many people were in each division.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In ref. [30], the authors used infrared (IR) sensors to calculate the number of people inside a building, installing sensors on the doors' tops to detect transit movement between rooms, so they could calculate how many people were in each division.…”
Section: Related Workmentioning
confidence: 99%
“…Case Study Why Was Chosen [23] Hand gesture detection Image data extraction using OpenCV [24] Video processing on Raspberry PI OpenCV on Raspberry PI [25] Human facial recognition OpenCV on Raspberry PI [27] Extraction of vehicle information OpenCV on Raspberry PI [28] Surveillance system Image acquisition on Raspberry PI [29] Indoor/outdoor person detection Uses RFID tags to detect humans [30] Indoor human detection Uses infrared sensor to detect humans [31] Indoor monitoring Uses IoT devices with AI IndoorCare Indoor human monitoring Uses IoT devices with Computer Vision…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed, implemented, and evaluated their system and demonstrated that the proposed magnetic field-based system is much more reliable than previously proposed Bluetooth-based approaches. Another possible solution for monitoring people in indoor environments was introduced by Perra et al [ 34 ]. The proposed device implements a novel real-time pattern recognition algorithm for processing data sensed by a low-cost infrared (IR) array sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Though its range is much shorter than sound-based ranging sensor, infrared sensor triumphs in resolution and higher distance measurement rate [18]- [19]. Using a group of infrared sensors can provide an effective full coverage of the robot's path at a cheaper price than laser-based and radarbased sensors [20]- [21].…”
Section: Introductionmentioning
confidence: 99%